RESPONSE OF INDUSTRIAL POTATOES TO BIOLOGICAL AND CHEMICAL FERTILIZERS AND BRASSINOLIDE IN ABSORBING ELEMENTS AND SOME QUALITATIVE TRAITS - Abbass AL Shammery; I. J. Abdulrasool2 (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2026)
ABSTRACTThe experiment was carried out at southwest Baghdad during fall season 2021 and spring season 2022 on the industrial potato of Arsenal hybrid, and the experiment carried out using randomized complete block design with in split plot arrangement with three replicates (4 × 3 × 3). Bio-fertilizer distributed within main plots and interaction between phosphorus levels and Brassinolide growth regulator within sub plot. Bio-fertilizers included Aspergillus niger fungus alone and Bacillus Megaterium bacteria alone and the combination between them add the control and phosphorus treatment of three levels of 0.100, 200 kg P2O5 ha-1 and Brassinolide spraying of three levels of 0, 0.1, 0.2 mg L -1, The results showed a significant effect of the triple interaction among study factors, where the interaction between fungal and bacterial Bio-fertilization and phosphate fertilization 200 kg h-1 and spraying at a concentration of 0.1 mg L-1 with Brassinolide growth regulator had a significant effects, it gave the highest significant value in the percentage of phosphorus, potassium and iron concentration of leaves for both seasons and nitrogen percentage for the fall season with (0.45, 0.51 and 1.74, 1.74%, 130.00, 138.67 ppm and 1.31%) respectively, while the combination between fungal and bacterial Bio-fertilization and, phosphate fertilization 200 kgP2O5 h-1 and spraying at a concentration of 0.2 mg L-1 with Brassinolide growth regulator had the highest nitrogen percentage in the spring season 1.30% as well as produced the highest dry matter percentage, starch and protein in tubers for both seasons (21.00, 21.83 and 14.72, 15.64 and 1.79, 1.87%) respectively.